Analisis Aspek Hukum dan Kendala Penegakan Hukum Pada Kasus Kebakaran Lahan Berdasarkan Putusan Nomor 71/PID.B/LH/2021/PN SNT - Ni Kadek Juwita Widyastiti; Komang Febrinayanti Dantes; I Wayan Empu Guana Pura; I Gusti Ayu Apsari Hadi (Jurnal Ilmu Hukum Sui Generis, 2025)
This paper aims to identify and analyze the case of land fires caused by the negligence of PT. Mega Anugrah Sawit (MAS) based on Decision Number 71/PID.B/LH/2021/PN SNT. In cases of corporate negligence resulting in environmental damage, an analysis of how this occurred, how it was handled, and how the judge's decision was rendered to ensure recovery from all damages incurred is necessary. Corporations whose operations do not comply with applicable procedures and legal provisions in Indonesia can be considered a crime, requiring criminal sanctions to create a deterrent effect so that acts of environmental damage are not repeated in the future. The problems of this research are the chronology of the case, what legal aspects were violated, who the legal instruments involved, and what obstacles to environmental law enforcement in this case are. The methodology applied in this research is normative juridical. Based on the analysis that has been conducted, it is observed that there are several legal aspects, legal instruments, and obstacles in law enforcement in this land fire case. Thus, criminal law becomes the main instrument in resolving these legal problems.